DEIXIS SOSIAL PADA SATUA BALI “PAN BALANG TAMAK” - I Made Subur; I Ketut Subagia; I Wayan Ana; Dewa Ayu Dyah Pertiwi Putri (Universitas Warmadewa, 2025)
Deixis is part of pragmatics, which functions as a pointer. The pointer in question is any form of language used to refer to people, places, times, or specific situations. This study is highly dependent on the context and situation in a statement, so its use cannot be separated from the social and cultural background of the speaker. Cultural background is a major factor influencing the form and use of deictics. In line with this, Indonesia is known as a multicultural country with 718 regional languages, which certainly influences the forms of deictics. One form of the actualisation of regional language use can be seen in the arts, particularly in traditional literary works such as satua bali. In Balinese satua, sor singgih basa is generally used, which is a language variety that reflects differences in politeness levels. The existence of sor singgih basa influences the form of deictic expressions used, as their use is adapted to the social status and relationship between the speaker and the addressee in the story. This study uses a qualitative method with a Balinese satua entitled Pan Balang Tamak as data source. Data was collected through observation techniques and analysed using a qualitative approach. The analysed data consists of narrative excerpts and the utterances of the characters in the story. The results of the study indicate that two forms of deictic expressions were found: relational social deictic expressions and absolute social deictic expressions.